LITERASI PEMBUKUAN USAHA MIKRO DAN KECIL BATIK CIREBON DESA KALITENGAH KECAMATAN TENGAH TANI KABUPATEN CIREBON - Lukman, Hendro; Patricia, Virginia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Every business needs accounting records and reports. This also applies to Micro, Small and Medium Enterprises (MSMEs). If you look at the applicable provisions, the meaning of MSMEs is measured by the size of the business's net assets and its circulation or gross sales. With applicable regulations, businesses entering MSMEs must be measured by financial reports. The problem with Cirebon Batik UKM in